HUBUNGAN KECANDUAN INTERNET DENGAN GEJALA DEPRESI PADA REMAJA - Prihayanti, Ni Komang Trisna; Swedarma, Kadek Eka; Nurhesti, Putu Oka Yuli (Coping: Community of Publishing in Nursing; Vol 9 No 3 (2021): Juni 2021, 2021)
One mental disorder which happens among adolescents is depression. Nowadays, one cause of depression among adolescents is internet addiction. This research to determine the correlation between internet addiction and depression symptoms among adolescents at Senior High School 2 Denpasar. This study was a descriptive correlation with a cross-sectional design. Stratified random sampling was used to determine 100 samples. Internet Addiction Test (IAT) and Beck Depression Inventory (BDI) were used in this study. The results show that the majority of respondents using the internet to access social media, using smartphones as the main device to access the internet, firstly use the internet at  ? 12 years old for men and at <12 years old for women. First, use the internet at <12 years old for respondent age before 16 years old and at  ? 12 years old for respondent age after or on 16 years old. Most of the respondents use the internet for 4-6 hours. Most of the respondents have moderate internet addiction and the majority don’t have any symptoms of depression. The correlation between internet addiction and depression symptoms among adolescents is a significant and weak correlation with a positive direction with a p-value of 0.012 (p <0.05; r = 0.252), it is mean that internet addiction has a correlation with depression symptoms among adolescents at Senior High School 2 Denpasar. This study can be a base for parents to pay more attention to internet usage and use the internet properly.